PENERAPAN MODEL GUIDED INQUIRY BERBANTUAN MEDIA POP-UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SD N 1 SELAT - Putu Budi Utami; I Nengah Sueca; Putu Beny Pradnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to measure the implementation and improvement of science learning outcomes on the material of changes in the state of matter through the Guided Inquiry learning model assisted by Pop-Up Book media in fourth-grade students of SD N 1 Selat. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart spiral design which includes the planning, implementation, observation, and reflection stages. The research subjects consisted of 11 fourth-grade students of SD N 1 Selat in the even semester of the 2025/2026 academic year. Data were collected through test techniques in the form of cognitive evaluation and non-test techniques in the form of observation of learning activities. The results of the study showed a significant increase in students' science learning outcomes. In the pre-cycle conditions, the average class score was only 57.00 with a classical completeness of 27.27% (3 out of 11 students completed). After being given action in Cycle I, the average class score increased to 73.64 with a classical completeness of 45.45% (5 out of 11 students completed). Furthermore, the improvement actions in Cycle II succeeded in increasing the class average score to 85.45 with a classical completion of 81.81% (9 out of 11 students completed). This achievement has met the classical completion success indicator set at 80% based on the Learning Objective Achievement Criteria (KKTP) 75. Thus, the implementation of the Guided Inquiry model assisted by Pop-Up Book media is effective in improving the learning outcomes of elementary school students in science.